2019
DOI: 10.1111/nicc.12414
|View full text |Cite
|
Sign up to set email alerts
|

The effects of noise levels on nurses in intensive care units

Abstract: Background Intensive care units (ICUs) are noisy environments, which may have negative psychological effects on nurses. Aims and objectives To investigate the effects of the noise level of ICUs on nurses' burnout, job satisfaction, anxiety, psychological symptoms and general psychopathology level. Design A descriptive and correlational study. Methods The study was conducted with 150 intensive care nurses. A Type 2250‐L Brüel & Kjær hand‐held sound level meter was used for noise measurement. A Nurse Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 32 publications
4
36
0
16
Order By: Relevance
“…Mean SAI scores were significantly higher at a shift time of 4:00 pm to 12:00 am when noise levels in the ICU were 61 to 70.99 dB compared with noise levels of 60.99 dB(A) and below and 71 dB and above ( P < .01) (Table 3). 10 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean SAI scores were significantly higher at a shift time of 4:00 pm to 12:00 am when noise levels in the ICU were 61 to 70.99 dB compared with noise levels of 60.99 dB(A) and below and 71 dB and above ( P < .01) (Table 3). 10 …”
Section: Resultsmentioning
confidence: 99%
“…Cvach reported a significant increase in noise levels in hospitals since the 1960s 4 . Several studies have also reported that noise levels in intensive care far exceed World Health Organization (WHO) thresholds 5‐10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study could show that the staff's job satisfaction and anxiety levels were significantly associated with noise measurements at their ICU. 47 Attempts to implement behavioral changes to reduce noise levels are certainly necessary, but alone, they have thus far been ineffective. 48 Behavioral-based interventions may only be effective when supplemented by innovative tools, and there is a growing number of technological and architectural solutions that can aid the implementation of acoustics in the hospital setting as a prophylactic or therapeutic measure.…”
Section: Sound and Icu Environmentmentioning
confidence: 99%
“…Terzi et al . () surveyed 150 nurses, in a variety of critical care units to assess the impact of noise levels on the nurses' satisfaction and emotional well‐being. Using a wide range of appropriate instruments, including a self‐report inventory and symptom checklist, the results identified that noise levels were the highest in neonatal, neurological, and cardiovascular units, exceeding 71 dB(A) or above (40 dB is normal).…”
mentioning
confidence: 99%